O ensino industrial-manufatureiro no Brasil - Luiz Antônio Cunha (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2000)
The article presents the origin and the development of the training of works for manufactures and factories in Brazil, since eighteenth century. Its central thesis is that the prejudices against manual work represent the main determinant of the underevaluation of the professional schools, as well as the dual educational system within the country. Since 1942, SENAI performed a new role in the brazilian industrial labor force training, in terms of students recruitment, pedagogy, management and financing. Nevertheless, in the recent years, that institution has lost the hegemony acquired in educational field, and prepares a package of importants decisions in order to prevent conflicts with State and labores syndicates.